Interpreting Charles Lamb’s ‘Neat-Bound Books’ - Wright, Laura; Langmuir, Christopher (Studia Anglica Posnaniensia, 2019)
In this paper we consider a much-quoted phrase published by the essayist Charles Lamb (1775–1834) in the London Magazine in 1822 about a desirable quality in books: that they should be ‘strong-backed and neat-bound’. We identify meanings of modifier neat as evidenced by different communities of practice in early nineteenth-century newspapers, and in particular we present meanings of neat as used in certain Quaker writings known to have been read with approval by Lamb. By this method we assemble a series of nuanced meanings that the phrase neat-bound would have conveyed to contemporary readers – specifically, the readership of the London Magazine.